JURNAL ANALISIS NILAI TUKAR MATA UANG TERHADAP MINAT INVESTASI DI INDONESIA - Fahirah (Jurnal Syariah dan Ekonomi Islam, 2025)
The exchange rate plays a crucial role in influencing investment interest in developing countries such as Indonesia. Exchange rate volatility affects investor confidence, capital inflows, and both real and financial sector investment decisions. This research aims to analyze how currency fluctuations impact investment interest in Indonesia, focusing on macroeconomic interrelations and investor behavioral responses. The method applied is descriptive qualitative, using secondary data derived from journal publications between 2020–2025. The findings indicate that currency depreciation tends to reduce investment interest due to increased uncertainty and asset devaluation. Conversely, stable exchange rates strengthen investment growth by enhancing investor confidence and reducing perceived risk. Therefore, exchange rate stability is essential to maintaining and increasing investment attractiveness in Indonesia.